COMPARATIVE STUDY ON THE REGULATION OF SHARIA FINANCIAL TECHNOLOGY IN INDONESIA AND MALAYSIA - Susilawati, Cucu; Sulaiman, Ahmad Azam; Abduh, Muhamad; Prasetyo, Yoyok; Athoillah, Mohamad Anton (Fakultas Syariah, 2021)
Financial technology is a part of digital ecosystem which development is rapid and massive, so does the sharia fintech. However, conventional and sharia fintech are two different systems and should have each regulation. The problem is if sharia fintech regulations in Indonesia is appropriate. Then what about Malaysia which are considered successful in developing the sharia fintech. This study compares sharia fintech regulations in Indonesia and Malaysia. The aim is to find out the readiness of Indonesia and Malaysia in supporting the sharia fintech trend realized in the regulations. This is a qualitative research using books and academic articles as an addition to the literature and regulations as the analytical method. The results indicate that Indonesia and Malaysia try to accommodate sharia fintech regulations. Indonesia still uses The Financial Services Authority Regulation (POJK) and Bank Indonesia regulations, both of which do not meet the sharia principles. Meanwhile, Malaysia uses the 2013 Islamic Financial Services Act (IFSA), a law to regulate sharia compliance of the Islamic financial services sector, including the Sharia Fintech. In addition, Malaysia also has a Sharia Advisory Council as a supervisor for the Islamic financial services implementations. Malaysiaâ€™s and Indonesiaâ€™s regulations have yet answered the sharia fintech developments.Â Financial technology merupakan bagian dari ekosistem digital yang perkembangannya sangat pesat dan masif, tak terkecuali fintech syariah. Namun, fintech konvensional dan syariah adalah dua sistem yang berbeda dan seharusnya memiliki peraturan yang berbeda pula. Permasalahannya apakah regulasi fintech syariah di Indonesia sudah tepat apa belum, lalu bagaimana dengan regulasi di Malaysia yang dianggap berhasil mengembangkan fintech syariah. Tujuannya adalah untuk mengetahui sejauhmana kesiapan Indonesia dan Malaysia dalam mendukung trend fintech syariah dalam regulasi. Penelitian kualitatif ini menggunakan buku dan artikel akademis sebagai tambahan literatur dan peraturan sebagai metode analisis. Hasil penelitian menunjukkan bahwa Indonesia dan Malaysia sama-sama berusaha mengakomodasi regulasi. Indonesia masih menggunakan Peraturan Otoritas Jasa Keuangan dan Peraturan Bank Indonesia, dan belum memenuhi prinsip syariah. Malaysia menggunakan Islamic Financial Services Act (IFSA) 2013, sebuah Undang-Undang yang mengatur kepatuhan syariah dari sektor jasa keuangan Islam. Malaysia juga memiliki Dewan Pertimbangan Syariah sebagai pengawas pelaksanaan jasa keuangan Islam. Regulasi yang dimiliki oleh Malaysia dan Indonesia belum menjawab perkembangan fintech syariah.